A study on relationship between service quality and customer satisfaction of Nasuha Enterprise Sdn. Bhd. at Pagoh / Norhaini Ghazali - Ghazali, Norhaini (Faculty of Business and Management, 2011)
This research of “A Study on Relationship Between Service Quality and Customers Satisfaction of Nasuha Enterprise Sdn. Bhd. “was conducted with 3 objectives which are to measure the current level of customers satisfaction toward services provided by Nasuha Enterprise Sdn. Bhd. at Pagoh, to determine the relationship between service quality dimensions of Nasuha Enterprise Sdn. Bhd. at Pagoh with the customer’s satisfaction and to recommend the best service quality elements that can be use by Nasuha Enterprise Sdn.Bhd. at Pagoh. The respondents of this study were the guest of Nasuha Enterprise Sdn.Bhd. at Pagoh and 150 questionnaires had been distributed. In this study, the descriptive statistics had been used to interpret the data such as reliability testing, frequency tables and correlation testing. From the finding, respondents agree with the satisfaction of service quality dimensions which provided by Nasuha Enterprise Sdn. Bhd. Pagoh. While the best dimensions of service quality is reliability dimension that satisfied customers. The reliability gained the highest value with 4.629. The results also show the relationship between the service quality and customers satisfaction. Besides that, Research also come out with some recommendation which is improve the services reliability, improve the assurance services and increase the services of Nasuha Enterprise Sdn. Bhd. Pagoh in order to make the service quality of Nasuha Enterprise Sdn. Bhd. become more effective and can create customer’s satisfaction. Then can create customers interest to deal with Nasuha Enterprise Sdn. Bhd.